Association of affect with vertical position in L1 but not in L2 in unbalanced bilinguals - Li, Degao; Liu, Haitao; Ma, Bosen (Frontiers in Psychology, 2015)
After judging the valence of the positive (e.g., happy) and the negative words (e.g., sad), the participants’ response to the letter (q or p) was faster and slower, respectively, when the letter appeared at the upper end than at the lower end of the screen in Meier & Robinson’ (2004) second experiment. To compare this metaphorical association of affect with vertical position in Chinese-English bilinguals’ first language (L1) and second language (L2) (language), we conducted four experiments in an affective priming task. The targets were one set of positive or negative words (valence), which were shown vertically above or below the centre of the screen (position). The primes, presented at the centre of the screen, were affective words that were semantically related to the targets, affective words that were not semantically related to the targets, affective icon-pictures, and neutral strings in experiment 1, 2, 3, and 4, respectively. In judging the targets’ valence, the participants showed different patterns of interactions between language, valence, and position in reaction times across the experiments. We concluded that metaphorical association between affect and vertical position works in L1 but not in L2 for unbalanced bilinguals.